2015
DOI: 10.1021/acs.jpcb.5b03801
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation Study of the Early Stages of Nucleation of Iron Oxyhydroxide Nanoparticles in Aqueous Solutions

Abstract: Nucleation is a fundamental step in crystal growth. Of environmental and materials relevance are reactions that lead to nucleation of iron oxyhydroxides in aqueous solutions. These reactions are difficult to study experimentally due to their rapid kinetics. Here, we used classical molecular dynamics simulations to investigate nucleation of iron hydroxide /oxyhydroxide nanoparticles in aqueous solutions. Results show that in a solution containing ferric ions and hydroxyl groups, iron-hydroxyl molecular clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 47 publications
5
37
2
Order By: Relevance
“…The catalyst prepared by method 3 provided a higher yield of O 2 (65 %) than the catalysts prepared by methods 1 and 2 (60 and 54 % of the stoichiometric yield, respectively). The results obtained can be understood based on the data reported by H. Zhang et al [27] who used the method of molecular dynamics for studying the process of the formation of primary particles of hydroxo compounds. The author established that disordered 1-2 nm hydroxide clusters are only formed at low concentrations of the hydrolyzed salts.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…The catalyst prepared by method 3 provided a higher yield of O 2 (65 %) than the catalysts prepared by methods 1 and 2 (60 and 54 % of the stoichiometric yield, respectively). The results obtained can be understood based on the data reported by H. Zhang et al [27] who used the method of molecular dynamics for studying the process of the formation of primary particles of hydroxo compounds. The author established that disordered 1-2 nm hydroxide clusters are only formed at low concentrations of the hydrolyzed salts.…”
Section: Resultsmentioning
confidence: 79%
“…[35] Some literature data were used for modeling the iron hydroxide cluster. Zhang and co-authors [27] used centroid molecular dynamics with combined set of force fields [36,37] and additional central force model for water [38] for modeling the process of nucleation of Fe III hydroxide. These simulation results showed that during the early stages of hydrolysis there is occurs the coagulation processes and formation of amorphous primary hydroxide particles (1-2 nm).…”
Section: Catalyst Modeling By a Molecular Mechanics Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…In many experimental settings, cluster-and particle-based pathways have been observed for iron() oxide nucleation and growth. 2,[5][6][7] In the early stages of iron() hydrolysis, small species in the size range of 1-4 nm occur. Such polymeric clusters aggregate to form the different crystalline materials.…”
Section: Introductionmentioning
confidence: 99%
“…Such polymeric clusters aggregate to form the different crystalline materials. 2,5,6,8 It was recently proposed that iron() (oxyhydr)oxide precipitation in such cluster-based pathways can be described within the notions of the so-called pre-nucleation cluster (PNC) pathway. 9 In this model, in contrast to the classical nucleation picture, a) J. Konsek, J. Schwaderer, and S. M. Stadler contributed equally to this work.…”
Section: Introductionmentioning
confidence: 99%